2009
DOI: 10.1038/nature08013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of activated pyrimidine ribonucleotides in prebiotically plausible conditions

Abstract: At some stage in the origin of life, an informational polymer must have arisen by purely chemical means. According to one version of the 'RNA world' hypothesis this polymer was RNA, but attempts to provide experimental support for this have failed. In particular, although there has been some success demonstrating that 'activated' ribonucleotides can polymerize to form RNA, it is far from obvious how such ribonucleotides could have formed from their constituent parts (ribose and nucleobases). Ribose is difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
1,271
0
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,203 publications
(1,297 citation statements)
references
References 28 publications
14
1,271
0
12
Order By: Relevance
“…Then, we comment on the fact that the origin of nucleosides is the weakest link in this possible chain of events. Recent findings suggest a solution [28], for conditions probably different from those that supposedly characterized prebiotic processes (namely: simplicity, robustness and availability of abundant precursors). Formamide chemistry allows the formation of acyclonucleosides in non-demanding conditions [29].…”
Section: (Pre)genetics and (Pre)metabolismmentioning
confidence: 92%
See 2 more Smart Citations
“…Then, we comment on the fact that the origin of nucleosides is the weakest link in this possible chain of events. Recent findings suggest a solution [28], for conditions probably different from those that supposedly characterized prebiotic processes (namely: simplicity, robustness and availability of abundant precursors). Formamide chemistry allows the formation of acyclonucleosides in non-demanding conditions [29].…”
Section: (Pre)genetics and (Pre)metabolismmentioning
confidence: 92%
“…On the basis of existing data, the direct condensation of sugar and natural nucleic bases does not work efficiently under prebiotic conditions either for kinetic and thermodynamic reasons [97]. Examples of the two other reaction pathways of possible prebiotic interest have been reported: 1) β-ribocytidine-2 ,3 -cyclic phosphate was synthesized with high stereoselectivity by a multistep process starting from glycoladehyde and cyanamide through a pentose amino-oxazoline derivative on which the cytosine scaffold was gradually built [28]. The use of amino pentose-oxazolines as intermediates in the synthesis of nucleoside derivatives is a well-known practice in medicinal chemistry [98].…”
Section: Plausible Syntheses Of Nucleosides In Prebiotic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…of hydrogen cyanide and formamide to nitrogen heterocycles; 67 the triose-ammonia reaction; 68,69 and the nucleoside synthesis recently suggested by Sutherland and co-workers. 70,71 Detailed studies of these and other abiotic reaction networks may help to elucidate common properties of reaction networks and differences from networks formed by evolution. Work along these lines is described in our companion publication.…”
Section: Probing the Chemistry Of The Formose Reaction Networkmentioning
confidence: 99%
“…12 On the other hand, the selective formation of ribose is rather a difficult process, and remained a matter of debate, even though a number of studies have shown that activated ribonucleotides polymerize to form RNA. Recently, this missing link has been addressed by the work of Powner et al 18 Their experiments have shown that activated pyrimidines ribonucleotides can be formed, bypassing free ribose and the nucleobases, starting from cyanamide, cyanoacetylene, glycolaldehyde, glyceraldehyde and inorganic phosphate, all plausible prebiotic feedstock molecules, and synthesis conditions that are consistent with early-Earth geochemical models.…”
Section: Introductionmentioning
confidence: 95%